2020
DOI: 10.1016/j.scs.2020.102413
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the exposure risk of SARS-CoV-2 in different hospital environment

Abstract: Highlights The exposure risk of SARS-CoV-2 in diverse environments in hospital was compared. The nucleic acid of SARS-CoV-2 in air and surfaces suggested the potential risk. It is necessary to monitor and disinfect the SARS-CoV-2 in hospital environment. Ventilation, sterilization may help to reduce the potential risk for HCWs. Different strategies were discussed in combating infectious disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
42
0
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 63 publications
(44 citation statements)
references
References 43 publications
0
42
0
2
Order By: Relevance
“…The coronavirus disease 2019 (COVID-19), caused by the severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) and first reported in December 2019 in Wuhan city of China, has soon become a new public health concern across the world ( Ge et al, 2020 ; Jin et al, 2020 ; Rumpler, Venkataraman, & Göransson, 2020 ; Sun & Zhai, 2020 ). The virus poses serious potential threats to the medical protection system all over the world ( European Centre for Disease Prevention & Control, 2020 ; World Health Organization, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…The coronavirus disease 2019 (COVID-19), caused by the severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) and first reported in December 2019 in Wuhan city of China, has soon become a new public health concern across the world ( Ge et al, 2020 ; Jin et al, 2020 ; Rumpler, Venkataraman, & Göransson, 2020 ; Sun & Zhai, 2020 ). The virus poses serious potential threats to the medical protection system all over the world ( European Centre for Disease Prevention & Control, 2020 ; World Health Organization, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…Wearing a mask is essential, particularly for those people who are at a greater risk of severe illness from COVID-19 diseases. It is found that the spread of COVID-19 is mainly among people who are in immediate contact with one another (nearly about 6 feet), it can be spread by people who do not have symptoms and are unaware of the fact that they are infected ( Ge et al, 2020 ). So Centers for Disease Control and Prevention (CDC) 1 recommended all people 2 years of age and older to wear a mask in public areas especially when other social distancing ( Sun & Zhai, 2020 ) measures are difficult to maintain.…”
Section: Introductionmentioning
confidence: 99%
“…In Xiangya Hospital (H-X), Chenzhou Second People’s Hospital (H-C), and Shaoyang Central Hospital (H-S), the exposure risk to SARS-CoV-2 was evaluated by Ge et al ( 2020 ). All air samples were collected for 30 min using the NIOSH BC251 bioaerosol sampler (National Institute for Occupational Safety and Health) and air pumps (XR5000, SKC) at 3.5 L/min.…”
Section: Air Sampling For Sars-cov-2 Detectionmentioning
confidence: 99%
“…Rooms with viral particles in the air also presented surface contamination Chia et al ( 2020 ) 33 air samples were collected for 30 min using the NIOSH BC 251 bioaerosol sampler (National Institute for Occupational Safety and Health) with air pumps (XR5000, SKC) at 3.5 L/min. The NIOSH sampler segregates air sample into large (≥ 4 μm), medium (1–4 μm), and small (< 1 μm) particles 7.7% and 82.6% of samples were positive for SARS-CoV-2 in COVID-19 respiratory investigation wards and ICUs with confirmed COVID-19 patients, respectively Ge et al ( 2020 ) 28 samples were collected using 2-stage cyclone samplers (NIOSH BC 251), filter cassette containing a Teflon® filter ( D = 37 mm and 2 μm porosity), and a sampling pump (PCXR-4, SKC, Eighty-Four, PA) at a flow rate of 3.5 L/min for 315–360 min All samples were negative for SARS-CoV-2 Lane et al ( 2020 ) Liquid impactors Air samples were collected in COVID-19 isolation rooms used for three patients with severe pneumonia, using a SKC BioSampler at 12.5 L/min and at 10 L/min, both for 20 min, placed 1.2 m from the floor, and at a 1-m distance from patients All samples were negative for SARS-CoV-2 Ahn et al ( 2020 ) 10 air samples were collected during 1 h, using a vacuum pump at 1.5 L/min, in SKC sterile standard midget impingers at a height of 1.5–1.8 m from the floor and at a distance of 2–5 m from beds of patients with severe and critical symptoms All samples were negative for SARS-CoV-2 Faridi et al ( 2020 ) Air samples were collected using a SASS 2300 wetted wall cyclone sampler (Research International, Inc., https://www.resrchintl.com ) at 300 L/min for 30 min SARS-CoV-2 was detected in air at a 4-m distance from patients Guo et al ( 2020 ) Air samples were collected using a high-volume WA 400 Portable viral aerosol sampler (Dingblue Tech, Inc.), at 400 L/min for 15 min SARS-CoV-2 was detected in 01 out of 02 air samples Jin et al ( 2020 ) Air samples were collected using the SKC impinger-type biosampler at a flow rate of 12 L/min, placed 1.5 m from the floor 02 out of 14 air samples were positive for SARS-CoV-2 Kenarkoohi et al ( 2020 ) 135 air samples were collected using an impinger sampler (BIO-Capturer-6, Bioenrichment Co., Hangzhou, China), for 30 min at 80 L/min, and placed 1.0–1.5 m from the floor All samples were negative for SARS-CoV-2 Li et al ( 2020 ) 26 air sam...…”
Section: Air Sampling For Sars-cov-2 Detectionmentioning
confidence: 99%